Convergence of primary education development in urban and rural China: empirical analysis of historical trends and future projections - Yan Zhang; Wei Yang; Bo Li; Yifan Yang; Liu Chen; Lu Feng (Humanities & Social Sciences Communications)
Abstract Integrating primary school education in urban and rural areas is essential for reducing disparities in resources and promoting educational equity. This study uses four analytical methods—entropy variation coefficient-comprehensive index, time difference correlation analysis, multivariate linear regression prediction, and Beta convergence—to analyze the historical evolution, future trends, and convergence in primary education development levels in China. Using national time series data from 1995 to 2022, we constructed an evaluation index for primary education and found that the urban-rural gap in primary education has slightly narrowed. Although urban growth currently surpasses rural growth, projections for the next 13 years suggest a decreasing gap in annual growth rates between the two. The analysis shows significant absolute Beta convergence nationally and within urban areas from 1995 to 2035, while rural areas exhibit divergence. After controlling for factors such as per-student expenditure, school building floor space per student, student-teacher ratio, teacher education level, teacher title structure, number of primary schools per student, enrollment rates, and dependency ratio, we find no significant conditional convergence at the national level or between urban and rural areas from 1995 to 2035. These results highlight that current levels of urban-rural investment are inadequate for balancing primary education development. To address this, increased and equitable educational investment is necessary for balanced development across urban and rural areas, within rural areas, and among urban regions.